Analysis of performance of asphalt pavements in Qatar using mechanistic-empirical approaches - K. Lakshmi Roja (14159028) (2023)
Qatar roads are experiencing heavy traffic loads due to the rapid increase in the country’s population and construction projects over the past two decades. Considering the demand for high-performing, sustainable, and cost-efficient pavements, emphasis has been placed on using different asphalt modifiers and recycled materials in pavement layers. These modifiers/recycled materials change asphalt mixture properties, and consequently, influence pavement performance. The main objective of this study is to evaluate the performance of pavement sections that incorporate various types of asphalt mixtures and are subjected to traffic levels that range from 5 to 200 million equivalent single axle loads (ESALs). The analysis of pavement performance was conducted via three methods: Australian pavement design method implemented in Circly software, perpetual pavement design using PerRoad software, and a simplified mechanistic-empirical pavement design method (MEPD) that utilizes performance models used in AASHTOWare. The outcome of these analyses was the selection of suitable combinations of asphalt mixtures as well as the optimization of pavement layer thicknesses for different traffic loads. The results highlighted that the use of a high-stiffness mixture incorporating modified asphalt (PG 82E-10) in the wearing course should be used with caution in high traffic load sections (≥100 million ESALs). These stiff layers could be susceptible to cracking when the underneath asphalt layers have much less stiffness (50–70% less stiffness). However, in the medium traffic level (10–50 million ESALs) sections, pavement performance improved by using a stiff mix incorporating a PG 82E-10 binder in the wearing course layer. In addition, the use of crumb rubber (CR) modified asphalt reduced the material cost of a pavement section relative to the use of polymer-modified binder. The results show that it is desirable to use French EME (Enrobés à Module Elevé) mix in the base course layer for heavy traffic roads as this mix help to reduce pavement layer thicknesses and overall material cost. The outcomes of the analysis showed that the rutting thresholds commonly used in MEPD method are too restrictive (low thresholds) for heavy-duty pavements in Qatar hot climate. It is recommended to increase the rutting thresholds for such pavements. Other Information Published in: Case Studies in Construction Materials License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.cscm.2022.e01708